An investigation into trends in frequency and proportion of different durations of various types of extreme precipitation in Iran - Hossein Asakereh; Saeideh Ashrafi (Meteorological Applications, 2023)
Abstract Climate change can be traced in any given region by searching for changes in climatic elements' characteristics. Extreme precipitation, for example, is a characteristic of precipitation whose changes, especially in recent years, can be attributed to global warming and climate change. This study aimed to investigate possible changes in extreme precipitation in Iran by analysing the frequency of extreme rainy days duration. To this end, gridded precipitation datasets from the hydrological years 1971–1972 to 2015–2016 were used, and days associated with extreme precipitation were extracted by using thresholds of 90th, 95th, and 99th percentiles (as heavy, very heavy, and extremely heavy precipitation, respectively). Latitude and longitude showed the most significant correlation with precipitation characteristics in the spatial distribution during the study period. In addition, heavy (HP), very heavy, and extremely heavy precipitation experienced durations of 1–8, 1–7, and 1–4 days, respectively. At all extremes, the 1‐day duration covered more areas and had more repetition, while the longer duration had the lowest tempo–spatial repetition. According to the results of the present study, the one‐day duration of HP contributed more significantly to the annual precipitation. The proportion of this type of precipitation has been more significant in the southern and central regions of the country. Furthermore, it was revealed that the frequency of durations of short‐term HP increased during the study period, whereas the duration of long‐term HP declined.